The role of protocol biopsies after pediatric kidney transplantation. Issue 23 (5th June 2020) - Kanzelmeyer, Nele K.; Lerch, Christian; Ahlenstiel-Grunow, Thurid; Bräsen, Jan H.; Haffner, Dieter; Pape, Lars
Abstract : Abstract: Data on protocol biopsies (PBs) after pediatric kidney transplantation are rare. We evaluated 6-month post-transplantation renal function in 86 children after PB as observational study. Patients were divided into 3 groups: PB pathological findings absent, no intervention (n = 44); pathological findings but stable serum creatinine so no intervention (n = 27); pathological findings (borderline rejection (borderline) Banff classification (Banff) Ia or IIa), increased serum creatinine 20%, therapy initiated (n = 15). Glomerular filtration rate (GFR) and delta GFR were determined. Group 1: Mean GFR was 79 mL/min/1.73 m 2 body surface area (BSA) (± 23) at time of biopsy. Six months after PB GFR was 75 mL/min/1.73m 2 BSA (± 24), delta GFR –4.7 and remained stable until 24 months when it decreased to 64 mL/min/1.73m 2 BSA (± 23), delta GFR –15.3. Group 2: Mean GFR was 83 mL/min /1.73m 2 BSA (± 26). 12 months after PB mean GFR decreased slightly (79 mL/min/1.73m 2 BSA (± 29), delta GFR –5.1) and by 24 months had decreased to 75 mL/min/1.73 m 2 BSA (± 27), delta GFR –9.6 (1 vs 2 P  = .54). Group 3: Mean GFR was lower, 59 mL/min/1.73m 2 BSA (± 23). Six and 12 months after PB mean GFR increased, but by 24 months it had decreased to 51 mL/min/1.73m 2 BSA (± 12), delta GFR +2.2 (1 vs 3 P  = 0.009, 2 vs 3 P = .035). PBs 6 months post-kidney transplantation did not influence the clinical course in stable pediatric patients and are therefore of questionable value. Decreased kidney function may however be stabilized by therapeutic intervention according to results of PB.